School Well-Being Reviewed from Interpersonal Relationships in Students - Apriliyani Kusuma Wardani; Sneha Sneha; Jewil Taslim; Beby Astri Tarigan; Winida Marpaung; Nur Afni Safarina (Mahesa Research Center, 2025)
This research was executed at SMP Swasta Raksana Medan. The purpose of this study was to determine the interpersonal relationship with school well-being in students of SMP Swasta Raksana Medan. A total of 119 students of SMP Raksana Medan were used as the population and in the study conducted. The sample was obtained through the use of the Disproportionate Stratified Random Sampling technique. Data collection was carried out through the distribution of questionnaires to all samples. Furthermore, it was analyzed through the use of multiple regression analysis. A real correlation was found between School Well-Being and Interpersonal Relationships, as evidenced by the F test obtained F = 24,840 and p = 0.000 (p <0.05). Assumption tests include normality tests and linearity tests. Data analysis was carried out through multiple linear regression analysis techniques assisted by SPSS Statistic 27 for windows software. The resulting research showed a real contribution of 18.3 percent from School Well-Being School well-being and interpersonal relationships, the remaining 81.7 percent came from other factors not studied. This finding means that higher School Well-Being can also make students' interpersonal relationships high. Conversely, low School Well-Being can also make students' interpersonal relationships low.